As implicações da psicomotricidade e sua avaliação em estudantes com altas habilidades/superdotação - Peixoto, Maria Beatriz Campos de Lara Barbosa Marins [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
Target audience of special education, students with high skills/giftedness demonstrate high potential in any one of the following areas, isolated or combined: intellectual, academic, leadership, psychomotricity and arts, in addition to presenting great creativity, involvement in learning and performing tasks in areas of their interest. The identification and assessment of these students involve a complex process. It is often started in the school context and needs specialized educational service, multimodal, composed of qualified professionals of Education and Psychology to assess and identify areas that must be enriched and properly worked in order to the students extend their high skills. One of the few identified and reported areas in research and studies in Brazil refers to the field of psychomotricity. It is an important area that has a triple dimension: cognition, affectivity and movement. Therefore, the aim of this study was to identify the performance of psychomotricity - through psychomotor assessment - of the students who are part of an extension project, which have already been evaluated by other instruments, such as intelligence tests, school performance, creativity and social skills, and identified with high skills/giftedness. Thus, participating students have undergone evaluation by means Rosa Neto Motor Development Scale, which has scales of classification as a tool for investigation of fine Motricity, global Motricity, balance, body schema, spatial organization, temporal organization and laterality and, yet, by the Test of Gross Motor Development-2 (TGMD2), which assesses motor coordination. Both are validated instruments used by education professionals... (Complete abstract electronic access below)

Público-alvo da educação especial, os estudantes com altas habilidades/superdotação demonstram potencial elevado em qualquer uma das seguintes áreas, isoladas ou combinadas: intelectual, acadêmica, liderança, psicomotricidade e artes, além de apresentar grande criatividade, envolvimento na aprendizagem e realização de tarefas em áreas do seu interesse. A identificação e a avaliação desses estudantes envolvem um complexo processo. Iniciado, muitas vezes, no contexto escolar, precisa de atendimento educacional especializado, multimodal, composto por profissionais qualificados da Educação e da Psicologia para avaliar e identificar áreas que, por direito, devem ser enriquecidas e adequadamente trabalhadas a fim dos estudantes ampliarem suas habilidades superiores. Uma das áreas pouco identificadas e relatadas em pesquisa e estudos no Brasil refere-se ao campo da psicomotricidade. Importante área que possui uma tríplice dimensão: a cognição, a afetividade e o movimento. Desse modo, o objetivo do presente trabalho consistiu em identificar o desempenho da psicomotricidade, por meio de avaliação psicomotora, dos estudantes que fazem parte de um projeto de extensão, que já foram avaliados por outros instrumentos, como testes de inteligência, desempenho escolar, criatividade e habilidade social, e identificados com altas habilidades/superdotação. Assim, os estudantes participantes passaram por avaliação por meio da Escala de Desenvolvimento Motor Rosa Neto, que possui escalas de classificação como instrumento de investigação da motricidade fina, motricidade global, equilíbrio, esquema corporal, organização espacial, organização temporal e lateralidade e, ainda, pelo Teste de Desenvolvimento Motor Global - TGMD2, que avalia a coordenação motora grossa. Ambos são instrumentos validados utilizados por profissionais da educação... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Psicomotricidade; Superdotados; Educação especial; Special education